2005
DOI: 10.1021/jp050294g
|View full text |Cite
|
Sign up to set email alerts
|

IR Spectroscopy and Density Functional Theory of Small V+(N2)n Complexes

Abstract: V+(N2)n clusters are generated in a pulsed nozzle laser vaporization source. Clusters in the size range of n = 3-7 are mass selected and investigated via infrared photodissociation spectroscopy in the N-N stretch region. The IR forbidden N-N stretch of free nitrogen becomes strongly IR active when the molecule is bound to the metal ion. Photodissociation proceeds through the elimination of intact N2 molecules for all cluster sizes, and the fragmentation patterns reveal the coordination number of V+ to be six. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
65
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 41 publications
13
65
1
Order By: Relevance
“…Homoleptic dinitrogen complexes of genuine transition metals, such as tetra-coordinated Ni(N 2 ) 4 , hexa-coordinated vanadium, and chromium complexes M(N 2 ) 6 , have been synthesized and spectroscopically characterized in low-temperature matrices 69 . Mass spectrometric and infrared photodissociation spectroscopic investigations in the gas phase revealed that the Ti + , V + , and Nb + cations form six-coordinated dinitrogen complexes 1012 , while the Y + , La + , and Ce + cations gave the octa-coordinated dinitrogen complexes 13 . There is only one theoretical report on neutral octa-coordinated dinitrogen complexes by Kovacs, who calculated the lanthanum species La(N 2 ) n ( n = 1–8) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Homoleptic dinitrogen complexes of genuine transition metals, such as tetra-coordinated Ni(N 2 ) 4 , hexa-coordinated vanadium, and chromium complexes M(N 2 ) 6 , have been synthesized and spectroscopically characterized in low-temperature matrices 69 . Mass spectrometric and infrared photodissociation spectroscopic investigations in the gas phase revealed that the Ti + , V + , and Nb + cations form six-coordinated dinitrogen complexes 1012 , while the Y + , La + , and Ce + cations gave the octa-coordinated dinitrogen complexes 13 . There is only one theoretical report on neutral octa-coordinated dinitrogen complexes by Kovacs, who calculated the lanthanum species La(N 2 ) n ( n = 1–8) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Nb + (N 2 ) n and V + (N 2 ) n complexes were investigated using photodissociation spectroscopy. 28,29 Rh(N 2 ) 4 + complexes were studied by infrared laser photodissociation spectroscopy and theoretical calculations. 30 TiN 12 + was generated by laser ablation, and the most stable structure was found to be Ti(N 2 ) 6 + with O h symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Duncan and co-workers investigated In–N 2 and Al–N 2 complexes by photoionization spectroscopy, 16,17 and studied Mg + –N 2 , Ca + –N 2 , Nb + (N 2 ) n , and V + (N 2 ) n complexes using photodissociation spectroscopy. 18–21 Dagdigian and co-workers studied the electronic states of an Al–N 2 complex with laser-induced fluorescence spectroscopy. 22 …”
Section: Introductionmentioning
confidence: 99%